Radial Neck Fractures in Children: Results When Open Reduction Is Indicated - Falciglia, Francesco (J Pediatr Orthop, 2014)
BACKGROUND: Radial neck fractures in children are rare, representing 5% of all elbow pediatric fractures. Most are minimally displaced or nondisplaced. Severely displaced or angulated radial neck fractures often have poor outcomes, even after open reduction, and case series reported in literature are limited. The aim of the study is to analyze the outcomes of patients with a completely displaced and angulated fracture who underwent open reduction when closed reduction failed. METHODS: Between 2000 and 2009, 195 patients with radial neck fractures were treated in our institute. Twenty-four cases satisfied all the inclusion criteria and were evaluated clinically and radiologically at a mean follow-up of 7 years. At follow-up, the carrying angle in full elbow extension and the range of motion of the elbow and forearm were measured bilaterally. We recorded clinical results as good, fair, or poor according to the range of movement and the presence of pain. Radiographic evaluation documented the size of the radial head, the presence of avascular necrosis, premature physeal closure, and cubitus valgus. RESULTS: Statistical analysis showed that fair and poor results are directly correlated with loss of pronation-supination (P=0.001), reduction of elbow flexion-extension (P=0.001), increase of elbow valgus angle (P=0.002), necrosis of the radial head (P=0.001), premature physeal closure (P=0.01), and associated lesions (olecranon fracture with or without dislocation of the elbow) (P=0.002). DISCUSSION: In our cases, residual radial head deformity due to premature closure of the growth plate and avascular necrosis were correlated with a functional deficit. Associated elbow injury was coupled with a negative prognosis. In our series, about 25% of patients had fair and 20% had poor results. Outcomes were good in 55% and felt to represent a better outcome than if the fracture remained nonanatomically reduced with residual angulation and/or displacement of the radial head. This study reports the largest series of these fractures with a combination of significant angulation and displacement of the fracture requiring open reduction. We feel that open reduction is indicated when the head of the radius is completely displaced and without contact with the rim of the metaphysis.